IDH1 mutated prostate cancer with psammomatous calcifications: A case report and review of the literature - Gaskin, D.A.; Reid, A.; Depeiza, N.; Nebhnani, J.; Gaskin, P.S. (Human Pathology Reports, 2025)
We report a case of grade group 2, pT 3 N0 Mx prostate acinar adenocarcinoma with intratumoural psammomatous calcifications and IDH1 mutation. This is an emerging molecular subtype of prostate cancer associated with a propensity for higher grade and stage of disease. The index case was of intermediate grade but had locally advanced stage III disease.